Development of an assessment tool for repetitive tasks of the upper limbs (ART) - Ferreira, Jeremy; Gray, Mike; Hunter, Leanne; Birtles, Matthew; Riley, David (Sudbury, 2009)
"The prevention, control and management of work-related musculoskeletal disorders (WRMSD) are a priority for the Health and Safety Executive (HSE) and one of the key ways of improving occupational health in Great Britain. Health and Safety Executive (HSE) and Local Authority (LA) Inspectors play an important role in preventing WRMSD. As well as enforcing health and safety law, they provide advice on risk factors and control measures on a range of health and safety issues. To support this work, assessment tools are required that offer an intuitive and relatively quick process to screen workplaces for high-risk activities, raise awareness of risk factors, demonstrate the presence of risk, and recommend areas for improvement. The Manual handling Assessment Charts tool (MAC, Monnington et al., 2002) has been recognised as a useful process to screen workplaces for high-risk manual handling operations (Melrose et al., 2006; Lee and Ferreira, 2003; Tapley, 2002). The MAC tool is designed to identify and help assess high-risk manual handling operations (lifting, lowering, carrying and team handling). However, its scope is limited to manual handling of heavy items, which primarily present a risk of lower back disorders. There was a demand for a similar tool that Inspectors can use to screen more frequent handling of light loads or other repetitive tasks and the common physical risk factors in work that may contribute to upper limb disorders (ULDs). This led to the development of the assessment of repetitive tasks (or ART) tool."